Training and Assistance Classroom Action Research (CAR) for Teacher MA Manbaul Bayan Lombok Timur - Doyan, Aris; Susilawati, Susilawati; Zuhdi, Muhammad; Sahidu, Hairunisa (Universitas Mataram, 2019)
Abstract: This community service aims to provide insight into the knowledge of writing scientific papers in an effort to improve teacher professionalism. Training The methods used in community service activities are the lecture, discussion and question, and answer method. Results of community service activities overall it can be considered quite good, seen from the presence of trainees reaching 90% of the number of MA Manbaul Bayan East Lombok teachers. The implementation procedure in the classroom action research training was rated as well based on positive responses from the participants and the level of mastery of the participants reached 75% of all stages of the implementation of the Classroom Action Research.Keywords: Classroom Action Research, Training and Assistance